Información financiera del estado de situación económica de la empresa "Ditosa Touma" en la ciudad de Babahoyo durante el período 2021-2022 - Rizzo Riofrio, Blanca Korinna (2023)
This case study was conducted with the objective of analyzing the economic situation of the company "Ditosa Touma" in the city of Babahoyo during the period 2021-2022, through financial information, which will allow to know the economic reality of the company in order to make the best decisions for the improvement of the company. The research methodology used is of mixed approach, combining quantitative and qualitative approaches to obtain a deep understanding of the financial information of the company's statement of economic situation. The research adopts a descriptive approach to identify problems, using documentary and field research, which included a visit to the facilities and contact with the general manager, thus supporting the complete analysis of the institution's economic situation. The information obtained was crucial to the study, and the deductive method was used in collaboration with management to analyze the problems, which allowed us to reach well-founded conclusions and make an informed judgment on the company's financial management. As conclusions, the results of the study point to a critical weakness in the financial control of the "Ditosa Touma" company by not having a specific bank account to record cash expenditures. This deficiency poses substantial risks of detour of funds and unethical financial practices; also, the institution has weaknesses in terms of poor cash management, which could lead to liquidity problems and difficulties in meeting short-term financial obligations. Finally, recommendations for improvement in the development of its economic and financial activities were made.